2018
DOI: 10.1002/aenm.201802540
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effects of Double Cation Substitution in Solution‐Processed CZTS Solar Cells with over 10% Efficiency

Abstract: The performance of many emerging compound semiconductors for thin‐film solar cells is considerably lower than the Shockley–Queisser limit, and one of the main reasons for this is the presence of various deleterious defects. A partial or complete substitution of the cations presents a viable strategy to alter the characteristics of the detrimental defects and defect clusters. Particularly, it is hypothesized that double cation substitution could be a feasible strategy to mitigate the negative effects of differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
120
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 132 publications
(129 citation statements)
references
References 51 publications
(56 reference statements)
9
120
0
Order By: Relevance
“…The one-electron orbitals are sampled on a well-converged Γ-point-centered 3 × 3 × 1 k-point mesh that converges total energies to within 0.05 meV per atom on a 2 × 2 × 2 supercell of the conventional kesterite/stannite-Cu 2 ZnSnS 4 and stannite-Cu 2 CdSnS 4 . [22] In brief, the spin-coating solutions were made by dissolving an appropriate quantity of copper acetate hydrate, zinc acetate dihydrate, cadmium acetate dihydrate, tin chloride dihydrate, and thiourea in 2-methoxyethanol. Also, the framework to estimate the chemical potentials needed for calculating the various defect formation energies is detailed in a previous publication.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The one-electron orbitals are sampled on a well-converged Γ-point-centered 3 × 3 × 1 k-point mesh that converges total energies to within 0.05 meV per atom on a 2 × 2 × 2 supercell of the conventional kesterite/stannite-Cu 2 ZnSnS 4 and stannite-Cu 2 CdSnS 4 . [22] In brief, the spin-coating solutions were made by dissolving an appropriate quantity of copper acetate hydrate, zinc acetate dihydrate, cadmium acetate dihydrate, tin chloride dihydrate, and thiourea in 2-methoxyethanol. Also, the framework to estimate the chemical potentials needed for calculating the various defect formation energies is detailed in a previous publication.…”
Section: Methodsmentioning
confidence: 99%
“…In 2012, Chen et al reported a low formation energy for Cu Zn +Sn Zn and 2Cu Zn +Sn Zn in kesterites and also proposed their deleterious role of introducing deep defects and bandgap narrowing. [6,9,11,[20][21][22][23] Here, we study the role of the proposed performance-limiting defects Cu Zn +Zn Cu and 2Cu Zn +Sn Zn by systematically substituting cations in Cu 2 ZnSnS 4 as characterized by both experimental and theoretical methods. [19] Hence, based on theoretical calculations, the possible performance-limiting point defects in kesterites are proposed to be the Cu-Zn antisite Cu Zn +Zn Cu , and the deep-trap-level-inducing Sn-antisite 2Cu Zn +Sn Zn .…”
Section: Introductionmentioning
confidence: 99%
“…By comparing devices with CZTS w/ S powder vs CZCTS w/ S powder and CZTS w/o S powder vs CZCTS w/o S powder, two Cd‐alloyed recipes showed comprehensive improvements on current density ( J sc ), open voltage ( V oc ), fill factor ( FF ) and power conversion efficiency (PCE). Such improvements could be attributed to large grains, long carrier lifetime, suitable absorber/buffer layer conduction band alignment, large‐range elemental composition tolerance, all of which have been discussed elsewhere . By comparing devices with CZTS w/ S powder vs CZTS w/o S powder and CZCTS w/ S powder vs CZCTS w/o S powder, two S powder‐free recipes also showed comprehensive improvements on device parameters.…”
Section: Resultsmentioning
confidence: 80%
“…The champion cell with CZCTS w/o S powder achieved J sc of 21.48 mA cm −2 , V oc of 0.548 V, FF of 63.8% and PCE of 7.51%. Noted that this PCE is so far the highest report for sputtering‐free CZTS solar cell and is even higher than those of many reports of sputtering‐involved CZTS solar cells with solution‐processed absorber ,, , . To figure out the driving forces behind this significant improvement derived from using S powder‐free recipe, more characterizations and mechanism are discussed in detail.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation